Historical Dictionary of Woody Allen - Brigham, William (Rowman & Littlefield Publishers, 2019)
Woody Allen has accomplished that which no American filmmaker in the modern era has or perhaps ever will: directing to date 49 films (47 full-length theatrical releases, 1 short film in an anthology, and 1 television film), writing 42 of those films (and co-writing the remaining 7) and acting in 29 of them. Collectively, these films have earned Allen 4 Oscars (1 for Best Director; 3 for Best Screenplay), as well as another 6 Academy Award nominations for Best Director, 13 for Best Screenplay and 1 for Best Actor. Actors, members of his film staff, and his producers have received 7 Oscars and another 20 nominations. All told, his films have garnered 132 awards and another 209 nominations from American and international bodies. Historical Dictionary of Woody Allen contains a chronology, an introduction, a filmography, an appendix, and an extensive bibliography. The dictionary section has over 600 cross-referenced entries on the actors, actresses, cinematographers, editors, designers, and producers he’s worked with as well as his films and awards. This book is an excellent resource for students, researchers, and anyone wanting to know more about Woody Allen.